Training on Utilizing Technology in Writing and Publishing Poetry - Muntazar, T.; Hajar, Ibnu (Faculty of Cultural Studies, Universitas Brawijaya, 2025)
Poetry writers can express ideas and feelings in written form, and present a unity of imaginative language expression with a beautiful rhythm. In the digital era like today, the opportunity to write and publish poetry is wide open. Unfortunately, not all students can take advantage of this opportunity. This also happened to students who are Sanggar Seni Bakat Bumoe (SSBM) members at Bumi Persada University, Lhokseumawe, Indonesia. To solve this problem, this community service team carried out service by training SSBM students to utilize technology to write and publish poetry. Poetry writing training for SSBM students is carried out through three stages: planning, implementation and evaluation. The planning stage includes collecting data on SSBM students' knowledge and enthusiasm in writing and discussing SSBM leadership elements to prepare a training activity plan. The implementation stage includes explaining the nature of quality poetry and the opportunity to be accepted in print and electronic media. The implementation stage also includes mentoring students in writing poetry and checking and providing comments and suggestions on student poetry. After revising the poems according to the comments and suggestions, students were also asked to publish them on Instagram. At the evaluation stage, the service team conducted an evaluation and interviewed SSBM leaders and students regarding the implementation of the training. The results of the interviews showed that this training contributed to increasing the enthusiasm of SSBM students to write as well as increasing their knowledge and skills in writing and publishing poetry.